Unveiling The Structures of Feeling in Ann Patchett's Tom Lake - Santoso, Yafet Kurniawan; Supsiadji, Mateus Rudi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This thesis explores how Ann Patchett’s Tom Lake captures and expresses the unspoken emotional atmosphere of rural American life during the COVID-19 pandemic through the lens of Raymond Williams’s theory of the "structure of feeling." Focusing on the novel’s portrayal of small-town community, familial labor, and generational memory, the research examines how emotions like longing, resignation, care, and quiet agency shape character identity and social relationships. Using Williams’s cultural materialism as a theoretical foundation, the study reveals how Tom Lake reflects the lived experiences of individuals whose emotions are deeply entangled with historical and socio-economic change, yet often remain unarticulated. The cherry farm, as both a physical and emotional space, becomes the central site where the past and present converge, offering a poignant setting in which Lara and her daughters navigate memory, loss, and continuity. Through narrative analysis, this thesis argues that Patchett’s use of everyday life, particularly under crisis conditions, mirrors the emotional undercurrents of a transitional era. The novel does not dramatize suffering but instead reveals the quiet persistence of meaning and feeling in ordinary routines. The result of this study demonstrates literature’s capacity to render the emotional truth of a historical moment visible through subtle, shared, and deeply human experiences. Keywords: COVID-19, Cultural Materialism, Rural Life, Structure of Feeling